Evaluation the Moisture Susceptibility of Asphalt Mixtures Containing Demolished Concrete Waste Materials - Hala Hamza Nazal; Mohammed Qadir Ismael (Salehan Institute of Higher Education, 2019)
The distress of moisture induced damage in flexible pavement received tremendous attention over the past decades. The harmful effects of this distress expand the deterioration of other known distresses such as rutting and fatigue cracking. This paper focused on the efficiency of using the waste material of demolished concrete to prepare asphalt mixtures that can withstand the effect of moisture in the pavement. For this purpose, different percentages of waste demolished concrete (0, 10, 20, 30, 50, 70 and 100) were embedded as a replacement for coarse aggregate to construct the base course. The optimum asphalt contents were determined depending on the Marshall method. Then after, two parameters were founded to evaluate the moisture susceptibility, namely: the tensile strength ratio (TSR) and the index of retained strength (IRS). To achieve this, the indirect tensile strength test and the compressive test were performed on different fabricated specimens. The results show that mixtures with a higher percentage of demolished concrete possess higher optimum asphalt content as this parameter increased from 3.9 % for control mixture to 4.5 % for mixture with coarse aggregate that fully replaced by demolished concrete. This work indicated that optimum percent of waste demolished concrete that can be utilized in the asphalt mixtures is 30 %, whereas this percent recorded higher value of increased increments for TSR and IRS by 10.6 % and 7.9 % respectively.